Implementing an hospital accreditation programme in a context of NPM reforms: Pressures and conflicting logics - Conceição, A.; Picoito, C.; Major, M. (Public Money and Management, 2024)
This article examines how an accreditation programme emerged and developed in a hospital in the context of New Public Management reforms. A case study demonstrates that healthcare organizations characterized as contested can self-transform into aligned ones. Accreditation programmes can provide the means to do this. Quality assurance practices and technical medical expertise coexisted as the initiative did not interfere with doctors’ independence and identity. Committed leadership was vital, particularly having a medical professional leading the project. As well, trust was an essential mechanism for effective collaboration between professionals, thus preventing resistance to change.